A review of imaging modalities for the hip - Weber, Alexander E. (Springer US, 2013)
Hip arthroscopy is one of the fastest growing surgical procedures performed by orthopaedic surgeons, with the number of hip arthroscopies expected to double in 2013. The increase in surgical prevalence is at least in part due to an increased awareness of prearthritic hip pathology. The diagnoses of prearthritic hip conditions are made through a comprehensive history, physical examination, and selection of appropriate diagnostic imaging modalities. The purpose of this review article is to provide the practicing orthopaedic surgeon with an overview of the imaging modalities available for the diagnosis of prearthritic hip pathology, with a focus on literature supporting advancements in imaging techniques and new applications of existing modalities.